2014
DOI: 10.1371/journal.pone.0105764
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Expression Profiling Shows that BRG1 Transcriptionally Regulates UV Inducible Genes and Other Novel Targets in Human Cells

Abstract: UV irradiation is known to cause cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6–4) pyrimidone photoproducts (6-4PPs), and plays a large role in the development of cancer. Tumor suppression, through DNA repair and proper cell cycle regulation, is an integral factor in maintaining healthy cells and preventing development of cancer. Transcriptional regulation of the genes involved in the various tumor suppression pathways is essential for them to be expressed when needed and to function properly. BRG1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Besides the mutagenic, DNA damaging and cell cycle disturbing actions of UV, the ultraviolet stress response involves the transcriptional regulation of many target genes (Sesto et al, 2002;Zhang et al, 2014;Valéry et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the mutagenic, DNA damaging and cell cycle disturbing actions of UV, the ultraviolet stress response involves the transcriptional regulation of many target genes (Sesto et al, 2002;Zhang et al, 2014;Valéry et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…No change in Ub genes expression was detected at these different UV doses at the two time points investigated, with respect to mock-treated cells (data not shown). To assess the efficacy of the treatment, we amplified as positive control interleukin 8 (IL-8), which was found to be a UV inducible gene in two whole genome expression studies (Sesto et al, 2002;Zhang et al, 2014): IL-8 mRNA markedly accumulated (~7.2-fold) 24 h after HeLa exposure to 100 J/m 2 . In the next experiments, HeLa cells were irradiated with higher UV doses (400 and 800 J/m 2 ), besides 100 J/m 2 , as above, and samples collected 4 h after treatment.…”
Section: Ubiquitin Genes Response Under Uv-induced Genotoxic Stress Cmentioning
confidence: 99%
“…Recent evidence has suggested that chromatin plays a major role in the UV-induced cellular response including regulation of gene expression changes (Andrade-Lima et al, 2015;Dawes et al, 2014;Dinant et al, 2013;Duan and Smerdon, 2014;Hassan et al, 2014;Izhar et al, 2015;Li et al, 2014;Sesto et al, 2002;Zhang et al, 2014). However, a detailed genomewide analysis to investigate the relationship of chromatin and gene expression changes was still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that epigenetic mechanisms also play a role in the transcriptional response following UV irradiation. For example, the components of the ATP-dependent SWI-SNF chromatin remodeling complex BRG1 and BRM (also known as SMARCA4 and SMARCA2, respectively) have been implicated in the transcriptional regulation of UV-induced genes (Hassan et al, 2014;Zhang et al, 2014). Furthermore, many posttranslational histone modifications have been shown to be modulated during the cellular response to DNA damage (Corpet and Almouzni, 2009;Kumar et al, 2012;Li et al, 2014;Tjeertes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…SWI/SNF complexes mobilize histone octamers in an ATP-dependent manner to allow or repress gene transcription1718. Loss of SMARCA4 expression changes approximately 5% of the mammalian transcriptome19, including changes in the expression of genes associated with NSCLC12, increasing the likelihood for loss of functions that might be redundant in normal cells and non-redundant in tumours lacking SMARCA4.…”
mentioning
confidence: 99%